Desempeño laboral de los colaboradores de la “tenencia política de la Parroquia Pimocha” - Piza Mayorga, Meybelin Deyaneira (2022)
The purpose of this case study is to know the performance of the collaborators of the political tenure of the Pimocha parish, in which it was carried out to verify each of the irregularities that occur in the institution, all this with respect to job performance. of the collaborators of the same, in fact the methodology was used in a descriptive way because it allowed to analyze the shortcomings of the company, the bibliographical references were also taken into account to support concepts, followed by an interview conducted directly with the manager of the company that He is the political lieutenant of the Parish.